The Impact of Russia–Ukraine Conflict on the Crude Oil Prices - Imeri, Amir; A. Gil-Alana, Luis; Monge, Manuel (International Journal of Energy Economics and Policy, 2026)
This paper investigates the properties of the crude oil prices in the context of the Ukraine- Russia conflict by using statistical techniques based on long memory and fractional integration. In order to understand the volatility of West Texas Intermediate crude oil prices, data from Federal Reserve Bank of St. Louis for the period September 12, 2012 to September 12, 2022 are used. The results using unit root tests indicate nonstationarity I(1) for the whole sample period but also for the two subsamples created by the war. Additionally, the findings through ARFIMA approach for the whole period as well as pre-Russia-Ukraine war period confirm mean reversion and transitory shock, whereas for the period from the start of Russia-Ukraine war, the shock in crude oil prices is expected to be permanent. There is a need for inter-governmental cooperation in keeping the oil price at its normal value.